PHYSICAL THERAPY AND PUBLIC HEALTH - Arsh, Aatik; Darain, Haider (Annals of Allied Health Sciences, 2019)
Physical therapy is closely related to public health because physical therapy is used in the prevention and management of many public health related issues. In 2016 Forouzanfar et al. gathered global data and reported 30 major public health issues in term of disability adjusted life years (DALY) and years of life lost (YLL). In current paper, role of physical therapy in the prevention and management of leading 30 global risk factors for DALY and leading 30 causes of YLL are discussed. The first and most important risk factor for DALY is high blood pressure. Though physical therapy interventions can’t be used directly to treat high blood pressure, however physical therapy exercises can help in preventing and controlling high blood pressure. Thus, physical therapy has role in the utmost important public health issue i.e. high blood pressure. The second leading risk factor for DALY is smoking. Smoking directly affects lungs and thus badly affects overall health of the individual. However, smokers who perform regular aerobic exercises have good respiratory parameters i.e. vital capacity etc. as compared to those smokers who have sedentary lifestyle. Another important risk factor for DALY is high fasting plasma glucose. Not surprisingly, physical activity improves quality of life of diabetes patients and helps in controlling high plasma glucose. The fourth leading risk factor for DALY which is increasing day by day is high body mass index. Indeed, obesity is alarmingly increased in past few decades. Obviously, physical activity including aerobic exercises and specific strengthening exercises are the main strategies for preventing high body mass index. Other leading risk factors for DALY in which physical therapy protocols can be used are high total cholesterol, low physical activity, and occupational ergonomic and occupational injuries. One of the most important causes of YLL in modern world is ischemic heart disease. There is not enough evidence to support the fact that whether physical activity and exercises can prevent, treat or minimize complications of ischemic heart disease. However, in general practice physical activity is always advised to some extent in ischemic heart disease. Another major cause of YLL is cerebrovascular disease. Physical therapy interventions such as motor relearning program, constraint induced movement therapy, gait training etc. are the main rehabilitation protocols for patients with cerebrovascular disease. Diabetes, which is associated with incredible human sufferings due to its sufferings, is also a leading cause of YLL. Physical activity only not helps in controlling diabetes but also improve quality of life by minimizing complications. Falls, which are common due to balance problems, is one of the leading causes of YLL. Balance training is a major domain of physical therapy rehabilitation which can prevent falls geriatric population and in those with compromised balance. Other leading causes of YLLs in which physical therapy protocols can be used are Lower respiratory infection, Chronic obstructive pulmonary disease (COPD), Tuberculosis and lung cancer, neonatal preterm birth complications, neonatal encephalopathy, neonatal sepsis, congenital anomalies, Meningitis, chronic kidney disease, liver, stomach and breast cancer, road injuries and alzheimers disease. To sum up, it can be concluded that physical therapy has role in prevention and management of major public health issues. In some leading risk factors and conditions, physical therapy has direct role in prevention and management e.g. occupational ergonomic and cerebrovasuclar diseases while in some conditions it has adjunct role e.g. COPD and respiratory infections.